EFFECT OF TEMPERATURE ON SURVIVAL DURING THE FIRST MONTH OF LIFE IN THE FIELD VOLE, MICROTUS ARVALIS, RAISED UNDER DIFFERENT CONDITIONS OF DAYLIGHT RATIO AND FEEDING - Martinet, Lise; Daketse, Marie-José; Garnier, Viviane (HAL CCSD, 1976)
International audience